Kompetensi Manajerial Kepala Sekolah dalam Meningkatkan Kinerja Guru di SMP Islam Al-Azhar 24 Kota Makassar - Nur, Dwi Utami Hidaya (Arus Jurnal Pendidikan, 2026)
It is the purpose of this study to determine the description of the principal's managerial competence in improving teachers’ performance in SMP Islam Al-Azhar 24 Makassar and to find out the supporting and inhibiting factors of the principal's managerial competence. This study is a descriptive qualitative research. The source of the data was obtained from the school principal, vice principal and teachers at SMP Islam Al-Azhar 24 in Makassar City. Data collection techniques used were interviews, observation and documentation. This study found that planning, organizing, implementing and supervising were strategies applied by the principal during his leadership time in schools to improve teachers’ performance in classroom learning. The principle prepared school activities programs and engaged teachers and staff to participate in the program during the drafting process, hence teachers’ competencies can be honed better as well as their performance. The improvements implemented not only in learning time but also in the school activity. In addition, maximizing the use of facilities and infrastructure for teachers and the implementation of program activities in order to improve teacher performance were the principle’s main concern for the sake of teachers’ performance. In the principal's managerial competence there were also factors that support and inhibit it. Principal's leadership, solid teamwork, organized work systems and school conditions or situations are factors that support the principal in implementing his managerial competence in the school. Whilst, for the inhibiting factors such as situational or conditions; like the appearance of competitors, make the principal felt more challenged in improving his managerial competence for the better.